Composition and distribution of odonata larvae and its relationship with physicochemical water quality in northern peninsular Malaysia - Ab. Hamid, Suhaila; Md. Rawi, Che Salmah; Abdul, Nurul Huda (University of Malaya, 2016)
A study on composition and distribution for Odonata larvae and their relationship with physicochemical parameters was carried out in selected rivers of Gunung Jerai Forest Reserve, Kedah. Different river physichochemical parameters might influence or affect different type of Odonata composition. Therefore, Odonata larvae were sampled monthly at three selected rivers in Gunung Jerai Forest Reserve which were Teroi, Tupah, Batu Hampar rivers from August 2007 until January 2008 by using a D-frame aquatic net. A total of 253 individuals of 12 genera belonging to nine families of Odonata have been identified. Greatest number of odonates individuals was recorded in Teroi River (112 individuals) with mean density recorded highest in January 2008 (6.6 ind/m2). The major families were Libellulidae, Euphaeidae and Gomphidae. Aeshnidae, Macromiidae, Calopterygidae, Coenagrionidae, Amphipterygidae and Chlorocyphidae represented the minority groups. Libellulidae reported the greatest number of individuals in all study areas, followed by Euphaeidae. Ranking from the highest to the lowest number of genus collected were Zygonyx, Euphaea, Macromia, Anax, Ophiogomphus, Libellago, Vestalis and Devadatta, Neurobasis, Cercion, Pseudagrion, Gamphidictinus, and Paragamphus. The distribution of these genera were significant in different months studied (Kruskal Wallis, p<0.05) in all three rivers. The abundance of individuals collected was strongly influenced by velocity of water. Libellulid Zygonyx was the most affected by velocity and biochemical oxygen demand in all studied river. A Euphaea larva was influenced by temperature, depth, pH and biochemical oxygen demand. The ecological index (Richness, diversity and evenness index) exhibited poor Odonata communities in all studied rivers. In conclusion, water velocity, biochemical oxygen demand do have influenced on Libellulidae family while temperature, depth, pH and biochemical oxygen demand have influenced on Euphaeidae family.